Contribuciones a la formación sociopolítica de futuros profesores de ciencias en el contexto colombiano: hacia una utopía posible - Hoyos, Nelson Enrique [UNESP] (2024)
This research examines the contribution of sociopolitical education to the initial training of science teachers. The teachers are considered agents capable of increasing their knowledge through intentional and systematic strategies that enables them to assume an active role in transforming social inequality conditions. The school is identified as a conducive environment for building a more humane and equitable society. Furthermore, scientific knowledge is recognized as a human activity that facilitates the understanding of socioscientific phenomena, thereby contributing to the consolidation of critical perspectives. In this research, a content analysis of the main documents of three physics education programs in Colombia was conducted. It was evident that, generally, these pedagogical projects are based on the perspective of technical rationality, with some elements of practical rationality, regarding the training of future graduates. The results of this study highlighted the need to integrate aspects aimed at promoting sociopolitical education in future science teachers within the curricula of initial training programs. Therefore, the implementation of a course titled "The Sociopolitical Education of Science Teachers" was proposed, with objectives and scopes designed to discuss the conception of school, the role of the teacher, and scientific knowledge. Through class recordings, reflective journals of students, and semi-structured interviews, the question was formulated: "How does the sociopolitical education course for science teachers provide future teachers with the opportunity to strengthen their reflexive identity?" The analyses identified the potential of creating a course with intentional and systematic actions so that future teachers progressively advance in levels of reflexivity and critical thinking that reflects their sensitivity to social conditions and their actions to transform them. The importance of introducing strategies such as case studies, reflective pairs, and writing reflective journals, in the context of these training course, was validated. This enhanced the reflexive identity of the future teacher. The empirical evidence allowed for theoretically and methodologically constructing the sociopolitical education component in the physics education program, through five nodal courses that visualize the epistemological references that make up this vision of training for the future physics teacher, who reconstructs their education under the utopia of a society .possible for all.